2014
DOI: 10.1021/cm500832h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Search for Design Principles of New Electron Accepting Polymers for All-Polymer Solar Cells

Abstract: New electron withdrawing monomers, thieno­[2′,3′:5′,6′]­pyrido­[3,4-g]­thieno­[3,2-c]­isoquinoline-5,11­(4H,10H)-dione (TPTI) and fluorenedicyclopentathiophene dimalononitrile (CN), have been developed and used to form 12 alternating polymers having different monomer combinations: (a) weak donating monomer–strong accepting monomer, (b) weak accepting monomer–strong accepting monomer, (c) weak accepting monomer–weak accepting monomer, and (d) strong donating monomer–strong accepting monomer. It was found that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 59 publications
3
98
0
Order By: Relevance
“…[94,95] The latter is therefore also linked to solubility. [94,95] The latter is therefore also linked to solubility.…”
Section: Frontier Molecular Orbitals (Homo Lumo)mentioning
confidence: 99%
“…[94,95] The latter is therefore also linked to solubility. [94,95] The latter is therefore also linked to solubility.…”
Section: Frontier Molecular Orbitals (Homo Lumo)mentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Only in the last two years, larger PCEs (4-6%) have been reported. However, both systems normally show poor PCEs o3% or around 3%.…”
Section: Introductionmentioning
confidence: 99%
“…Several criteria for designing electron accepting polymers for all-polymer solar cells were suggested. 26 It was suggested that accepting polymers should exhibit proper energy levels, internal 2 polarization and high electron mobility for high OPV performance.…”
Section: Introductionmentioning
confidence: 99%